Peran Corporate Social Responbility (CSR) Terhadap Citra Perusahaan Studi pada PT Timah Tbk di Kota Pangkalpinang Tahun 2023 - Septiyana, Ana; Julia, Julia (Pascasarjana STIE Amkop Makassar, 2025)
Corporate Social Responsibility (CSR) is a company's activity to be responsible for achieving profit, community welfare and environmental sustainability. Related to the case that highlighted PT Timah Tbk which had an impact on the company's reputation and image to be negative in the community. CSR can also be used as a strategy in creating and strengthening the company's image. CSR can provide a positive stigma in the form of a good reputation for the community so that the company's CSR efforts can attract great attention from existing customers and the community.This study aims to obtain empirical evidence of the role of Corporate Social Responsibility (CSR) on the corporate image of PT Timah Tbk in Pangkalpinang City in 2023 according to stakeholder perspectives. The number of informants used in this study was 5 people. The method used in this study is a descriptive method and qualitative analysis with a research focus on the role and perspective of stakeholders on corporate image through CSR programs that have been implemented by PT Timah Tbk. Data collection techniques using interviews, observations and documentation.This study concluded that there is a negative stigma from the community regarding the phenomenon involving the company's image becoming negative. However, the community is still greatly helped by the CSR program run by a very good company. With this, the company gets and has a positive image because of the role of CSR according to the perspective of the CSR recipient community in Pangkalpinang City because the company always runs the CSR program well and on target so that the community feels very helped by the program.Keywords: Role of Corporate Social Responsibility (CSR), community perspective, corporate image.